Surgical Treatment of Thoracic Aortic Aneurysms in Patients with Congenital Heart Disease - Bobylev, Dmitry; Boethig, Dietmar; Breymann, Thomas; Mathoni, Annika; Horke, Alexander; Ono, Masamichi (The Thoracic and Cardiovascular Surgeon, 2015)
Background This study we evaluate our results for surgical treatment of thoracic aortic aneurysms in patients with congenital heart disease.Patients and Methods Fifty patients aged between 12 and 71 years were treated for 51 thoracic aortic aneurysms. Forty-four of the patients developed aneurysms in the ascending aorta and seven developed aneurysms in the descending aorta. The underlying diseases for ascending aortic aneurysms included 16 congenital aortic stenosis, 16 bicuspid aortic valves, 4 transposition of the great arteries, 3 tetralogy of Fallot, 2 truncus arteriosus communis, and 3 other diseases. Patients with connective tissue disorders were excluded. All descending aortic aneurysms developed late after coarctation repair. The time interval between the correction and aneurysm operations was 15 years in ascending aneurysms and 28 years in descending aneurysms.Results The operative procedures for 44 ascending aortic aneurysms included 38 ascending aortic replacements, with or without aortic valve replacement (including 31 conduits), and 6 David operations. Graft replacement was undertaken for the seven descending aortic aneurysms. There were two hospital deaths. Forty-eight hospital survivors were in New York Heart Association functional class II or less at follow-up, which was conducted up to a maximum of 8 years after the procedure. All patients were free from reoperation and thromboembolic events. Aortic valve function was good in all six patients after the valve-sparing operation.Conclusion Thoracic aortic aneurysms in patients with congenital heart disease is highly associated with bicuspid aortic valve and aortic coarctation. For ascending aortic aneurysms, conduit replacement is the method of choice. The David procedure provides good results in selected patients. For descending aortic aneurysms, graft replacement is the preferred procedure. The relatively late development of thoracic aortic aneurysms indicates that long-term follow-up in patients with congenital heart disease, especially in patients with bicuspid aortic valve and aortic coarctation, is essential.
Keywords: thoracic aortic aneurysm; aortic root; aortic valve; repair; congenital heart disease